Determination of significant prognostic factors in the development of magnesium deficiency in children and adolescents with gastroesophageal reflux disease - Potapenko, S. V. (Journal of Education, Health and Sport, 2020)
The aim of the work is to determine the factors of the course of GERD in children and adolescents which are important for predicting the development of magnesium deficiency. Materials and methods of research. For the study 77 people aged 9 to 14 years, who have gastroesophageal reflux disease with endoscopically positive diagnostic result, were examined. All children who were involved in the study underwent laboratory tests of serum magnesium, intracellular (erythrocyte) magnesium, and calcium levels. The ratio of calcium and intracellular magnesium was also considered as an indicator of latent magnesium deficiency. Magnesium level in patients with GERD were compared with control group, which consisted of 20 children without GERD. The odds ratio and confidence intervals for a large number of anamnestic, clinical and instrumental factors of GERD were calculated to determine significant prognostic factors for the development of magnesium deficiency, after which the indicators of the relative risk and the minimum and maximum predictive coefficients for these factors were determined. Based on the indicators of the minimum and maximum prognostic coefficient, a range of the probability of magnesium deficiency in patients with GERD was formed. Results. Based on the determination of the level of serum, erythrocyte magnesium, and the ratio of Ca/Mgerythrocyte in children of the control group, who were practically healthy, the standard deviation (δ) was calculated, and the corridors of laboratory parameters corresponding to the normal level of magnesium, indicators of latent deficiency (from δ to 2δ) and indicators of deficiency of magnesium (more than 2δ) were determined. In the group with GERD normal magnesium levels were discovered in 41.6% of children. A total of 19.5% of patients had latent magnesium deficiency and 39% of children had magnesium deficiency. For the analysis were selected: hyperacidity (pH 0.86-1.59), which had an odds ratio of 3.47; the reflux esophagitis 2-3 stages with an odds ratio of 68.64; an increase in LF and HF values day and night, an increase in the daytime LF/HF ratio, an increase in the stress index, an increase in PAPR and average circadian index values. Based on the indicators of the minimum and maximum prognostic coefficient, a range of the probability of magnesium deficiency in patients with GERD was formed. With the sum of the predictive coefficients of each significant factor from 13.3 to 31.0, the probability of magnesium deficiency is low; the range from 31.1 to 48.8 corresponds to the average probability, and the range of 48.9 to 66.5 indicates a significant possibility of a magnesium deficiency in a patient with GERD. Conclusion. It was determined that the factors of hyperacidity and the reflux esophagitis, some indicators of heart rate variability (LF and HF day and night, an increase in the daytime LF/HF ratio, an increase in the stress index, an increase in PAPR and average indicators of the circadian index) can be used to predict the development of magnesium deficiency in children with GERD. The practical application of the predictive coefficients of the given factors will make it possible to timely correct magnesium deficiency and will positively affect the quality of GERD treatment in children and adolescents.